2019
DOI: 10.1016/j.jclinepi.2018.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Rapid reviews may produce different results to systematic reviews: a meta-epidemiological study

Abstract: Objective To simulate possible changes in systematic review results if rapid review methods were used. Study Design and Setting We recalculated meta-analyses for binary primary outcomes in Cochrane systematic reviews, simulating rapid review methods. We simulated searching only PubMed, excluding older articles (5, 7, 10, 15, and 20 years before the search date), excluding smaller trials (<50, <100, and <200 participants), and using the largest trial only. We examined pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 37 publications
1
81
1
Order By: Relevance
“…For the stopping prediction task, CLF could significantly reduce the cost of screening with tolerable losses in recall. The results of the stopping prediction task demonstrate the applicability of CLF to specific systematic reviews where total recall is not essential, such as in rapid reviews [34].…”
Section: Discussionmentioning
confidence: 77%
“…For the stopping prediction task, CLF could significantly reduce the cost of screening with tolerable losses in recall. The results of the stopping prediction task demonstrate the applicability of CLF to specific systematic reviews where total recall is not essential, such as in rapid reviews [34].…”
Section: Discussionmentioning
confidence: 77%
“…Records' titles and/or Digital Object Identifiers (DOIs) were used to check the index status of each study in the platforms. Where studies were indexed in a platforms, we treated them as retrieved by searches of that platform because our interest was not in the performance of search strategies actually used, rather the risk of sole reliance on studies that were indexed in the platforms (hence findable) 19 . This approach was chosen because applying the original search strings might miss studies indexed in the platforms 19 .…”
Section: Methodsmentioning
confidence: 99%
“…Where studies were indexed in a platforms, we treated them as retrieved by searches of that platform because our interest was not in the performance of search strategies actually used, rather the risk of sole reliance on studies that were indexed in the platforms (hence findable) 19 . This approach was chosen because applying the original search strings might miss studies indexed in the platforms 19 . To enable subgroup analyses, we also checked study sources and classified those into: (a) commercially published article; and (b) grey literature and unpublished data by applying the Luxembourg definition of grey literature: “manifold document types produced on all levels of government, academics, business, and industry in print and electronic formats that are protected by intellectual property rights, of sufficient quality to be collected and preserved by libraries and institutional repositories, but not controlled by commercial publishers” 25 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search will be conducted in English and will include studies published between the 01 st of January of 2000 and June 2020. The rationale behind the search from year 2000 to 2020 is ndings from a meta-analysis study which showed that searches including articles from the last 20 years did not result in the loss of any primary study [35].…”
Section: Methodsmentioning
confidence: 99%